Membangun Spirit Keagamaan di Desa Purnakarya: dari Penguatan Ibadah hingga Pemberdayaan Masyarakat: Fostering Religious Spirit in Purnakarya Village: from Strengthening Worship to Empowering the Community - Bakry, Kasman (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
The implementation of the Community Service Program (KKN) by STIBA Makassar in Desa Punakarya aims to enhance students' capacity to directly apply Islamic legal knowledge (syariat) together with the community, especially in remote and marginalized areas. This program also seeks to provide tangible support for local government initiatives, particularly in the fields of religious guidance and social community development. The implementation methods include work program workshops, scheduling and conducting imam duties and sermons, fiqh studies, social service activities, mass ruqyah and cupping therapy counseling, the Shaleh Children Festival, and teaching in schools. The results of the programs and activities show a success rate of 90%, indicating that the activities designed by the students effectively address community needs and have a profound positive impact on fostering religious spirit and empowering the village community.